Correlation Between Temporomandibular Joint Disorders and Bruxism: A Systematic Review and Meta-analysis (Bangladesh Journal of Medical Science, 2024)
Background The common conditions bruxism and temporomandibular joint disorders (TMD) have a major impact on dental health and quality of life. Even though both disorders have been thoroughly examined, there is still discussion and research surrounding their association. Objective The purpose of this study was to investigate the relationship, possible risk factors, and therapeutic consequences of the interaction between bruxism and TMD. Methods To summarize the available data on the relationship between bruxism and TMD, a thorough literature review was carried out. Furthermore, information was gathered to look at the connection between TMD symptoms and self-reported bruxism. We searched several databases for the relevant literature. These included; PubMed, Cochrane Google Scholar, etc. Following the inclusion and exclusion criteria a group of researchers collaborated to “include” and “exclude” the studies and a total of n=11 studies were considered for final review and analyses. Results The primary endpoint of the current analysis was to evaluate the correlation between temporomandibular joint disorders and bruxism. 10/11 (91%) of the studies advocated for a significant correlation; whereas, only 1/11 (9%) favored that there is a negative association between the two. The overall Odds ratio value was =5.66, CI=95% (4.63-6.91). The overall heterogeneity was found to be Tau2=0.05; Chi2=26.00; df=8; I2=69%. The overall effect size was found to be, Z=16.97 (p